Faktor-faktor yang berhubungan dengan tingkat kecemasan pasien usia dewasa pra-ekstraksi gigi di Puskesmas I Denpasar Selatan dan Puskesmas II Denpasar Utara, Bali-Indonesia - Putu Cita Anindika Restudiva; I Gusti Agung Sri Pradnyani; Desak Nyoman Ari Susanti (Bali Dental Journal, 2020)
Background: Dental anxiety is a multisystem response to threats or hazards that are believed by the individual and occurs when the patient comes to the dentist. The first trigger of patient anxiety in dental care is tooth extraction. The aim of the study is to identify factors related to pre-extraction dental anxiety levels, including sex, age, education, marital status, previous dental experience, and waiting room ambience. Method: This was an observational analytic study with cross-sectional design. Subjects were 76 people. Assessment of pre-extraction dental anxiety levels was measured using Dental Anxiety Scale (DAS). The factors related to the anxiety level is analyzed by using Chi Square test. Binary logistic regression test was used to determine the factors that have the greatest relationship with pre-extraction dental anxiety level. Result: there was a relationship between sex, age, previous dental experience, and waiting room ambience with pre-extraction anxiety levels (p=0.000; p=0.002; p=0.000; p=0.001). Educational factors and marital status have no relationship with anxiety level (p = 0.617; p=0.059). The result of binary logistic regression test showed that previous dental experience factor had the greatest relation with anxiety level (OR = 12) and statistically significant (p=0.001). Conclusion: factors related to the anxiety level of adult pre-extraction adult patients are gender, age, previous dental experience and waiting room ambience. Previous dental experience is the factor that has the greatest influence compared with other factors studied. Latar belakang: kecemasan dental merupakan respon multisistem terhadap ancaman atau bahaya yang diyakini oleh individu dan terjadi saat pasien datang ke dokter gigi. Pencetus pertama kecemasan pasien pada perawatan gigi adalah tindakan ekstraksi. Tujuan dari mengetahui faktor-faktor yang berhubungan dengan tingkat kecemasan pra-ekstraksi gigi, meliputi jenis kelamin, usia, pendidikan, status marital, pengalaman dental sebelumnya, dan suasana ruang tunggu. Metode: penelitian ini merupakan penelitian Observasional analitik dengan rancangan cross-sectional. Subjek penelitian berjumlah 76 orang. Penilaian tingkat kecemasan pra-ekstraksi gigi diukur menggunakan Dental Anxiety Scale (DAS). Uji faktor-faktor yang berhubungan dengan tingkat kecemasan menggunakan Chi Square test. Uji regresi binary logistic digunakan untuk mengetahui faktor yang memiliki hubungan paling besar dengan tingkat kecemasan pra-ekstraksi gigi. Hasil: ada hubungan antara jenis kelamin, usia, pengalaman dental sebelumnya, dan suasana ruang tunggu dengan tingkat kecemasan pra-ekstraksi (p=0,000; p = 0,002; p = 0,000; p = 0,001). Faktor pendidikan dan status marital tidak memiliki hubungan dengan tingkat kecemasan (p=0,617; p=0,059). Hasil uji regresi binary logistic menunjukkan faktor pengalaman dental sebelumnya memiliki hubungan paling besar dengan tingkat kecemasan (OR = 12) dan bermakna secara statistik (p=0,001). Simpulan: faktor-faktor yang berhubungan dengan tingkat kecemasan pasien usia dewasa pra-ekstraksi gigi di Puskesmas 1 Denpasar Selatan dan Puskesmas 2 Denpasar Utara adalah jenis kelamin, usia, pengalaman dental sebelumnya dan suasana ruang tunggu. Pengalaman dental sebelumnya merupakan faktor yang memiliki pengaruh paling besar dibandingkan dengan faktor lain yang diteliti.